Polymer-Based Hydrogel Loaded with Honey in Drug Delivery System for Wound Healing Applications - Siti Nor Najihah Yasin; Zulfahmi Said; Nadia Halib; Noor Izzati Mokhzani; Zulaiha A Rahman (MDPI, 2024)
Volume 15 Issue 14